Analysis of the Influence of the Number of Population, Wages, And HDI on Open Unemployment Rate in Central Java, 2016-2020: Analisis Pengaruh Jumlah Penduduk, Upah, dan Ipm Terhadap Tingkat Pengangguran Terbuka di Jawa Tengah Tahun 2016-2020 - Sari, Riana Julihan; Setyowati, Eni (Procedia of Social Sciences and Humanities, 2022)
Indonesia is one of the developing countries that has a major problem, namely the relatively high unemployment rate. This high unemployment rate causes an open unemployment rate. The purpose of this study was to determine the extent of the influence of population, wages, and the human development index on the open unemployment rate in Central Java Province in 2016-2020. The open unemployment rate is the dependent variable, while the population, wages, and the human development index are independent variables. This study uses a quantitative descriptive approach with secondary data obtained from the Central Statistics Agency for a period of 5 years starting from 2016-2020 consisting of 35 districts/cities. The analytical technique used is panel data regression analysis using Eviews 9 software.